Elektrische Widerstandsmessungen auf dem Grönländischen Inlandeis. - Hochstein, Manfred (Meddelelser om Grønland, 1965)
The electrical DC-resistivity measurements on the icecap of Greenland indicate that at depths greater than 300 m the resistivity of ice is 0.025-0.085 megohm m. These values are 103-104 times smaller than those from temperate glaciers. Laboratory tests as well as further field investigations demonstrate that the resistivity of cold sedimentary ice is a function of the temperature and the contact resistance between the grains. The contact resistance decreases exponentially with depth, resistivity variations at greater depths are therefore mainly caused by temperature variations. Temperatures calculated from resistivity measurements in Greenland show some correlation with theoretical temperatures.